2015
DOI: 10.4103/0973-1482.148692
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma arising in mature cystic teratoma with sigmoid invasion

Abstract: Malignant transformation in a mature cystic teratoma (MCT) is rare occurring in 1.8% out of 8000 cases of MCT. The most common histological types are squamous cell carcinoma (SCC) followed by adenocarcinoma and melanoma. Clinically, these tumors are usually asymptomatic but may be discovered accidentally during gynecologic examination due to mass effect. We present cytology and histology correlation of a rare case of SCC arising in a dermoid cyst with metastasis to sigmoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The patients are usually asymptomatic; although symptoms like abdominal pain and abdomino‐pelvic mass may be seen, similar to this case. It may be discovered accidentally during gynecologic examination due to mass effect . Acute intestinal obstruction may occur when there is adherence of a part of small bowel to the mass .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients are usually asymptomatic; although symptoms like abdominal pain and abdomino‐pelvic mass may be seen, similar to this case. It may be discovered accidentally during gynecologic examination due to mass effect . Acute intestinal obstruction may occur when there is adherence of a part of small bowel to the mass .…”
Section: Discussionmentioning
confidence: 99%
“…It may be discovered accidentally during gynecologic examination due to mass effect. 19 Acute intestinal obstruction may occur when there is adherence of a part of small bowel to the mass. 20 Advance cases may develop constitutional symptoms such as cachexia and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the different components of a teratoma, there can be various malignant transformations, such as squamous cell carcinomas (75%-80%), adenocarcinomas (7%), sarcomas (7%), basal cell carcinomas, sebaceous gland carcinomas, malignant melanomas, small cell lung cancers, transitional cell carcinomas, clear cell carcinomas, and gliomas [1,[3][4][5][6] . The patholog-ical diagnosis confirmed that this case was a teratoma accompanied by the malignant transformation of a sebaceous gland carcinoma, which is very rare.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors show up as off-white or light yellow and brittle, and they are often accompanied by bleeding and necrosis. A malignant transformation often occurs in the inner papilla of the cyst wall, near the nodules, in the inhomogeneous enhanced portion or the thickening cyst wall [3,4,13] . Therefore, surgeons should carefully examine the cyst wall of the specimen.…”
Section: Yun-xiao Zhou Et Al 24mentioning
confidence: 99%
See 1 more Smart Citation